Identifikasi morfologi dan rendemen kunyit (Curcuma domestica Val.) di Kecamatan Kamal dan Kecamatan Bangkalan, Kabupaten Bangkalan: Identification of morphology and yield of turmeric (Curcuma domestica Val.) in Kamal and Bangkalan Districts - Adisa, Shafira Desty; Tripatmasari, Mustika; Suryawati, Sinar; Wasonowati, Catur (AGROMIX, 2022)
Introduction: The increasing market demand for herbal medicines causes an increase in the demand for medicinal plants to meet the raw materials for herbal medicines. Therefore, it is necessary to increase the productivity of turmeric, especially on Madura Island, one of which is by taking a morphological approach to turmeric rhizomes to determine the differences in characters and also the yield of simplicia in Bangkalan Regency. This study aims to identify the morphology and percentage of turmeric rhizome yield in two locations in Bangkalan District, namely Kamal District and Bangkalan District. Methods: This study uses a survey method conducted in two sub-districts in Bangkalan District, namely Kamal District and Bangkalan District which were determined by purposive sampling based on the initial purpose of the study. Turmeric samples were taken using the Snowball sampling method to determine the location or sample points totaling 3 locations. Results: The results showed that the morphological characters of turmeric in both Kamal and Bangkalan sub-districts had similar characteristics, starting from the leaves, pseudo-stems and roots. The highest yield was in Kamal District, which was 16.35%, while in Bangkalan District the highest yield was 16.38%. Conclusion: There are no significant differences in the morphological characters of turmeric in Kamal and Bangkalan sub-districts due to almost the same biotic, abiotic and altitude conditions.